Anti-tumor activity of selective inhibitor of nuclear export (SINE) compounds, is enhanced in non-Hodgkin lymphoma through combination with mTOR inhibitor and dexamethasone. Issue 2 (28th December 2016) - Muqbil, Irfana; Aboukameel, Amro; Elloul, Sivan; Carlson, Robert; Senapedis, William; Baloglu, Erkan; Kauffman, Michael; Shacham, Sharon; Bhutani, Divaya; Zonder, Jeffrey; Azmi, Asfar S.; Mohammad, Ramzi M.
Abstract: In previous studies we demonstrated that targeting the nuclear exporter protein exportin-1 (CRM1/XPO1) by a selective inhibitor of nuclear export (SINE) compound is a viable therapeutic strategy against Non-Hodgkin Lymphoma (NHL). Our studies along with pre-clinical work from others led to the evaluation of the lead SINE compound, selinexor, in a phase 1 trial in patients with CLL or NHL (NCT02303392 ). Continuing our previous work, we studied combinations of selinexor-dexamethasone (DEX) and selinexor-everolimus (EVER) in NHL. Combination of selinexor with DEX or EVER resulted in enhanced cytotoxicity in WSU-DLCL2 and WSU-FSCCL cells which was consistent with enhanced apoptosis. Molecular analysis showed enhancement in the activation of apoptotic signaling and down-regulation of XPO1. This enhancement is consistent with the mechanism of action of these drugs in that both selinexor and DEX antagonize NF-κB (p65) and mTOR (EVER target) is an XPO1 cargo protein. SINE compounds, KPT-251 and KPT-276, showed activities similar to CHOP (cyclophosphamide–hydroxydaunorubicin–oncovin–prednisone) regimen in subcutaneous and disseminated NHL xenograft models in vivo . In both animal models the anti-lymphoma activity of selinexor is enhanced through combination with DEX or EVER. The in vivo activity of selinexor and related SINE compounds relative to 'standard of care' treatment is consistent with the objective responses observed in Phase I NHL patients treated with selinexor. Our pre-clinical data provide a rational basis for testing these combinations in Phase II NHL trials. Highlights: Earlier we demonstrated that targeting the nuclear exporter protein exportin-1 (XPO1) by a selective inhibitor of nuclear export (SINE) compound is a viable therapeutic strategy against Non-Hodgkin's Lymphoma (NHL) leading to Phase I evaluation of the lead SINE compound, selinexor, in NHL (NCT02303392 ). Here we studied combinations of SINE-dexamethasone (DEX) and selinexor-Everolimus (EVER) in NHL. The in vivo activity of selinexor and related SINE compounds relative to 'standard of care' treatment is consistent with the objective responses observed in Phase I NHL patients treated with selinexor and provide rational basis for testing these combinations in Phase II NHL trials.